2011
DOI: 10.1161/circulationaha.111.032961
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letter Regarding Article, “Intracoronary Versus Intravenous Administration of Abciximab in Patients With ST-Segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention With Thrombus Aspiration: The Comparison of Intracoronary Versus Intravenous Abciximab Administration During Emergency Reperfusion of ST-Segment Elevation Myocardial Infarction (CICERO) Trial”

Abstract: We thank Niccoli et al for their letter, which interestingly suggested that intracoronary administration of abciximab may exert its action in patients with ST-segment elevation myocardial infarction through facilitation of reversible no reflow. Our study was designed to detect a difference in electrocardiographic and angiographic measures of immediate myocardial reperfusion after primary percutaneous coronary intervention, markers that are frequently used in medium-sized randomized studies and show strong corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 5 publications
1
64
0
1
Order By: Relevance
“…mechanical thrombectomy combined with various intracoronary drugs) [5] and/or manual thrombectomy combined with distal filters [6] have been previously reported. Gp IIb/IIIa inhibitors and thrombolytics may not be very effective in such situations [7], probably having difficult access to glycoproteins 'masked' in the tightly packed thrombus. A hostile thrombus is frequently the harbinger of no-reflow, a severe compromise of epicardial blood flow despite successful relief of the infarct-related artery obstruction [8].…”
Section: Discussionmentioning
confidence: 99%
“…mechanical thrombectomy combined with various intracoronary drugs) [5] and/or manual thrombectomy combined with distal filters [6] have been previously reported. Gp IIb/IIIa inhibitors and thrombolytics may not be very effective in such situations [7], probably having difficult access to glycoproteins 'masked' in the tightly packed thrombus. A hostile thrombus is frequently the harbinger of no-reflow, a severe compromise of epicardial blood flow despite successful relief of the infarct-related artery obstruction [8].…”
Section: Discussionmentioning
confidence: 99%
“…Concerns, however, have been raised that they may also have deleterious effects by interfering with the reperfusion injury signaling pathways, leading to loss of endogenous cardioprotection especially after long-term Table 1 Pharmacologic agents used to reduce infarct size and proposed mechanism of action References Agent Proposed mechanism of action [13][14][15][16] Abciximab Inhibits platelet aggregation and leukocyte adhesion; improves microcirculation [17] Statins Conditioning promoting (by opening of mitochondrial ATP-sensitive channels) and anti-inflammatory effects [18] RAS inhibitors Reduce angiotensin II levels; reduce Ca 2 + overload [19] Anisodamine/ diltiazem Diltiazem: causes endothelium-mediated vasodilatation; reduces metabolic demand by negative inotropic and chronotropic effects; anisodamine: anticholinergic and α 1 -adrenergic receptor antagonist [20] Metoprolol Reduces myocardial oxygen consumption [21] Recombinant human SOD Free radical scavenger [22] Desferoxamine Iron chelator [23] Edaravone Free radical scavenger [24] Allopurinol Inhibitor of xanthine oxidase [25] Hu23F2G (LeukArrest)…”
Section: Statinsmentioning
confidence: 99%
“…34 The CICERO trial reported that there was a significant improvement in infarct size and myocardial reperfusion as assessed by myocardial blush among patients treated with IC abciximab compared with IV abciximab, though no difference was noted between the two groups in relation to myocardial reperfusion as assessed by resolution of ST segment. 38 Most recently, the Intracoronary Abciximab Infusion and Aspiration Thrombectomy in Patients Undergoing Percutaneous Coronary Intervention for Anterior ST Segment Elevation Myocardial Infarction (INFUSE-AMI) study demonstrated IC administration of abciximab delivered to the infarct lesion site resulted in a significant but mild reduction in infarct size in patients presenting with a large anterior STEMI. 39 There was not, however, any improvement in myocardial reperfusion, ST segment resolution, or 30-day clinical event rates, leaving the clinical utility of this therapy unclear.…”
Section: Glycoprotein Iib/iiia Inhibitors: Abciximab Eptifibatide Amentioning
confidence: 99%